Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.09.15.20195511
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inflammatory leptomeningeal cytokines mediate delayed COVID-19 encephalopathy

Abstract: SARS-CoV-2 infection induces a wide spectrum of neurologic dysfunction. Here we show that a particularly vulnerable population with neurologic manifestations of COVID-19 harbor an influx of inflammatory cytokines within the cerebrospinal fluid in the absence of viral neuro-invasion. The majority of these inflammatory mediators are driven by type 2 interferon and are known to induce neuronal injury in other disease models. Levels of matrix metalloproteinase-10 within the spinal fluid correlate with the degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 27 publications
3
27
0
2
Order By: Relevance
“…In addition to these reports from France, cumulative CSF results from patients with COVID-19 have been described by other authors, a few examples of which are noted here [ 224 , [281] , [282] , [283] ]. Espindola et al analyzed the CSF of 58 patients in Brazil with COVID-19 diagnosed via nasopharygneal SARS-CoV-2 PCR who had a variety of neurological complaints and found: 10 (17%) patients had a CSF WBC count >5 cells/μL (median 2 cells/μL (interquartile range (IQR) 1–4 cells/μL); 16 (28%) patients had CSF protein >45 mg/dL (median 35 mg/dL (IQR 25.8-48 mg/dL); 2 (3%) patients had detectable SARS-CoV-2 RNA in the CSF (one with persistent headache and one with acute disseminated encephalomyelitis); 3/38 (8%) patients had oligoclonal bands restricted to the CSF consistent with intrathecal IgG synthesis, 4/38 (11%) patients had matched CSF and serum oligoclonal bands while 31/38 (82%) patients had no oligoclonal bands; and median CSF neurofilament light chain was 1,694 pg/mL (IQR 1,091–3,358 pg/mL) and median CSF tau was 318.3 pg/mL (IQR 173-457.4 pg/mL) [ 281 ].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In addition to these reports from France, cumulative CSF results from patients with COVID-19 have been described by other authors, a few examples of which are noted here [ 224 , [281] , [282] , [283] ]. Espindola et al analyzed the CSF of 58 patients in Brazil with COVID-19 diagnosed via nasopharygneal SARS-CoV-2 PCR who had a variety of neurological complaints and found: 10 (17%) patients had a CSF WBC count >5 cells/μL (median 2 cells/μL (interquartile range (IQR) 1–4 cells/μL); 16 (28%) patients had CSF protein >45 mg/dL (median 35 mg/dL (IQR 25.8-48 mg/dL); 2 (3%) patients had detectable SARS-CoV-2 RNA in the CSF (one with persistent headache and one with acute disseminated encephalomyelitis); 3/38 (8%) patients had oligoclonal bands restricted to the CSF consistent with intrathecal IgG synthesis, 4/38 (11%) patients had matched CSF and serum oligoclonal bands while 31/38 (82%) patients had no oligoclonal bands; and median CSF neurofilament light chain was 1,694 pg/mL (IQR 1,091–3,358 pg/mL) and median CSF tau was 318.3 pg/mL (IQR 173-457.4 pg/mL) [ 281 ].…”
Section: Discussionsupporting
confidence: 66%
“…Remsik et al analyzed the CSF of 13 patients with cancer, COVID-19 and neurological symptoms [ 283 ]. None of the patients had a positive CSF SARS-CoV-2 PCR.…”
Section: Discussionmentioning
confidence: 99%
“…TNFRSF1B showed consistent expression changes in AD or AD-related pathologies, as well as in COVID-19 patient CSF samples. We also found that CXCL10 protein level was increased in CSF of COVID-19 patients [84] (Fig. 3b).…”
Section: Neuroinflammation-mediated Association Between Neuro-covid-1supporting
confidence: 54%
“…Similarly, neurotoxicity grade in ICANS correlates with CSF cytokine levels but not with CAR T‐cells in CSF 17 . In both conditions, CSF investigations revealed normal or mildly elevated cell counts with variable protein levels and elevated cytokine levels with molecular consistency across conditions 10,13,16,17,37,38,66 . Therefore, a cytokine‐mediated neuroinflammatory process has been suggested as the underlying pathogenic mechanism 5,10,12,14 …”
Section: Comparison Of Covid‐19‐related Encephalopathy and Icansmentioning
confidence: 99%
“…Additionally, CSF analysis, neuroimaging, and neuropathological findings, as well as the clinical response to various immunotherapies, are not consistent with an infectious disease targeting the brain but rather with an immune‐mediated pathogenesis 4,9–11 . Therefore, a cytokine‐mediated neuroinflammatory process, associated with cytokine storm, has been suggested as the underlying pathogenic mechanism 5,10,12–14 …”
Section: Introductionmentioning
confidence: 99%